Tying, Exclusivity, and Standard-Essential Patents - Hovenkamp, Erik (Science and Technology Law Review, 2018)
When a technological standard is adopted, implementers must pay to license all “standard-essential patents” (SEPs)—those patents covering core features of the standard—although the particular price terms usually cannot be negotiated before adoption. To allay implementers’ fear of being “held up,” SEP owners usually make commitments to offer licenses on “fair, reasonable, and nondiscriminatory” (FRAND) terms. Among other things, this acts as a contractual price control for SEP licenses, albeit an imprecise one that is subject to judicial interpretation. Aside from licenses, an SEP holder may further supply an important “collateral input”—one that is not subject to the FRAND pledge, but which implementers nevertheless require in order to market a viable product, such as a physical component. The SEP holder might tie its SEP rights to the collateral input. It might also engage in exclusive dealing or related practices, such as a “loyalty discounting” arrangement that imposes larger royalties on implementers who buy the input from competing providers. Importantly, FRAND pledges create a distinct impetus for tying and exclusive dealing: to circumvent the price control on licenses by diverting the desired markup to the collateral input. The result may be to foreclose competitors’ input sales. Such restraints have received little attention in the FRAND literature, but they are an emerging concern for innovation and competition policy. They have recently been attacked in two high-profile complaints filed against Qualcomm: one by the Federal Trade Commission and the other by Apple. Against this backdrop, this Article provides a legal and economic evaluation of tying and exclusive dealing arrangements in FRAND licensing. Such practices may act to undermine the FRAND price control, potentially violating the SEP holder’s commitment. The case for antitrust intervention is harder to make, but in principle the arrangement could act to exclude actual or potential competition in the collateral input market, bringing it within the scope of antitrust law. Several policy recommendations for how courts and standard setting organizations might address these tying and exclusivity arrangements are offered at the end of this Article